2015
DOI: 10.1177/1934578x1501000932
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Soil and Essential Oil Profiles in Salvia desoleana Populations: Preliminary Results

Abstract: Salvia desoleana is a herbaceous perennial shrub endemic of Sardinia (Italy). The leaves are a source of essential oil, used in pharmaceutical and cosmetic industries. The therapeutic function of this species has been associated to the presence of essential oils rich in α/β-pinene, p-cimene, linalool, linalyl acetate and 1,8-cineole. Today the industrial request of Salvia essential oils is increasing and most of the biomass is exploited from the natural populations which are under severe risk of genetic erosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…All samples (Q1–Q21) analyzed in this study showed different chemical compositions. One of the variables that most influences the chemical composition of the EO is type of soil [ 14 ]. The concentration percentage of the (E)-methyl cinnamate compound had a statistically significant difference ( p -value < 0.5) across the samples from different soil types and the percentage of trans-Caryophyllene did not present a significant difference in all samples ( p -value > 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…All samples (Q1–Q21) analyzed in this study showed different chemical compositions. One of the variables that most influences the chemical composition of the EO is type of soil [ 14 ]. The concentration percentage of the (E)-methyl cinnamate compound had a statistically significant difference ( p -value < 0.5) across the samples from different soil types and the percentage of trans-Caryophyllene did not present a significant difference in all samples ( p -value > 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…The physical and chemical properties of soil are one of the most determinants factors in various secondary products and could be involved in the EO composition in different species of aromatic plants (Melito et al 2013;Rapposelli et al 2015). Also, previous studies indicated that EO-bearing plants differ with various soil properties and the production of EO requires suitable soil for greater yield and better quality (Khalid et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Also, different chemotypes have been described for a number of medicinal plants [26][27][28][29]. Moreover, studies have shown that the different characteristics of medicinal plant may be affected by a variety of ecological factors such soil composition, temperature, humidity and other climatic conditions [30][31][32][33]. Consequently, these changes in content and composition would definitely affect the pharmacological activity of the essential oil.…”
Section: Introductionmentioning
confidence: 99%